Molecular detection of enteric viruses and the genetic characterization of porcine astroviruses and sapoviruses in domestic pigs from Slovakian farms - Slavomira Salamunova; Anna Jackova; Rene Mandelik; Jaroslav Novotny; Michaela Vlasakova; Stefan Vilcek (BMC Veterinary Research, 2018)
Abstract Background Surveillance and characterization of pig enteric viruses such as transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), rotavirus, astrovirus (PAstV), sapovirus (PSaV), kobuvirus and other agents is essential to evaluate the risks to animal health and determination of economic impacts on pig farming. This study reports the detection and genetic characterization of PAstV, PSaV in healthy and diarrheic domestic pigs and PEDV and TGEV in diarrheic pigs of different age groups. Results The presence of PAstV and PSaV was studied in 411 rectal swabs collected from healthy (n = 251) and diarrheic (n = 160) pigs of different age categories: suckling (n = 143), weaned (n = 147) and fattening (n = 121) animals on farms in Slovakia. The presence of TGEV and PEDV was investigated in the diarrheic pigs (n = 160). A high presence of PAstV infections was detected in both healthy (94.4%) and diarrheic (91.3%) pigs. PSaV was detected less often, but also equally in clinically healthy (8.4%) and diarrheic (10%) pigs. Neither TGEV nor PEDV was detected in any diarrheic sample. The phylogenetic analysis of a part of the RdRp region revealed the presence of all five lineages of PAstV in Slovakia (PAstV-1 – PAstV-5), with the most frequent lineages being PAstV-2 and PAstV-4. Analysis of partial capsid genome sequences of the PSaVs indicated that virus strains belonged to genogroup GIII. Most of the PSaV sequences from Slovakia clustered with sequences originating from neighbouring countries. Conclusions Due to no significant difference between healthy and diarrheic pigs testing of the presence of PAstV and PSaV provides no diagnostic value. Genetic diversity of PAstV was very high as all five lineages were identified in pig farms in Slovakia. PSaV strains were genetically related to the strains circulating in Central European region.